Integration of School Work Plans and Supervision in Improving the Effectiveness of School Management, Case Study of SDS IT Candra Buana - Tanti Fitri Yana; Asep Mulyana (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze the School Work Plan (RKS) and supervision practices in improving the effectiveness of school management at SDS IT Candra Buana. Through observation methods and in-depth interviews with teachers and school principals, this research identified the positive impact of integrating RKS and supervision on improving teacher performance and overall school management efficiency. The main finding of this research is that teachers' active participation in preparing RKS has a significant impact on the quality of school program planning. In addition, supportive supervision practices from the school principal help improve the implementation of the RKS according to plan. Good integration between RKS and supervision also contributes to better achievement of educational goals, because it ensures that every educational program is implemented effectively and school funds are used accountably.